DEVELOPMENT STRATEGIES OF ORGANIC RICE BUSINESS AT FARMER-OWNED ENTERPRISE, PENGAYOM TANI SEJAGAD INC, WONOGIRI - Putra A.F.L.; Darsono; Sutrisno J. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
Organic rice is believed to have many benefits for the body and the environment. Although the market opportunity for organic rice is good, it faces marketing problems. Hence, organic rice consumers are still limited. This study aims to formulate a strategy in the organic rice industry. The research method used is a combination research method, using Cohran test analysis tools and blue ocean strategy. The results showed that competition in the organic rice industry is in a red ocean. The recommended strategic innovation is to implement educational marketing methods, provide bulk organic rice, make alternative packaging bigger, collaborate with health consultants and implement a cashback system for farmers.